Total site heat integration targeting algorithm incorporating plant layout issues - Liew, Peng Yen (Elsevier, 2014)
Energy Efficiency has gained concern in the process industry due to the high energy consumption. Process Integration using Pinch Analysis plays an important role in enhancing the sustainability and the profitability margin of industrial processes. Total Site Heat Integration (TSHI) is one of the main branches of Process Integration based on Pinch Analysis technique, which is an industrial energy conservation strategy across individual process boundary. However, the pressure drop and heat loss on the steam mains have not been well discussed in the existing TS targeting methodologies. In this paper, an extended numerical algorithm is proposed for addressing the effects of plant layout to the minimum multiple utility targets. The extended tools are able to assist the designer to perform a preliminary assessment of the retrofit options for a steam system. This enhanced methodology improves the accuracy of the existing TS targeting methodology by considering the effects of plant layout in a TS system. The proposed methodology is demonstrated with an illustrative case study.